Prospects for Electric Mobility: Systemic, Economic and Environmental Issues - Ajanovic, Amela (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The transport sector, which is currently almost completely based on fossil fuels, is one of the major contributors to greenhouse gas emissions. Heading towards a more sustainable development of mobility could be possible with more energy efficient automotive technologies such as battery electric vehicles. The number of electric vehicles has been increasing over the last decade, but there are still many challenges that have to be solved in the future. This Special Issue "Prospects for Electric Mobility: Systemic, Economic and Environmental Issues" contributes to the better understanding of the current situation as well as the future prospects and impediments for electro mobility. The published papers range from historical development of electricity use in different transport modes and the recent challenges up to future perspectives.